Pengaruh Kombinasi Media Tanam Organik dan Nilai EC Larutan Nutrisi Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica narinosa L.H. Bailey) Varietas Pagoda pada Hidroponik Sistem Wick - Putra, Regi Widianto; Syah, Bastaman; Laksono, Rommy Andhika (UNIVERSITAS LABUHANBATU, 2023)
Broadbeaked Mustard (Brassica narinosa L.H. Bailey) or better known by other names Ta Ke Chai and Tatsoi has a beautiful appearance. This type of mustard is still relatively rare in the market even though some farmers have started cultivating it, its production and distribution are not as much as other types of mustard greens, and has a relatively higher selling price than the selling price of other mustard greens. The purpose of this study was to determine the effect of a combination of organic growing media and EC value of the nutrient on the growth and yield of Pagoda mustard in a hydroponic wick system. The study used a single factor randomized block design with 12 treatments, namely A (rockwool + EC 1.5-1), B (rockwool + EC 2.5-1), C (rockwool + EC 3.5-1), D (charcoal husk + EC 1.5-1), E (husk charcoal + EC 2.5-1), F (husk charcoal + EC 3.5-1), G (cocopeat + EC 1.5-1), H ( cocopeat + EC 2.5-1), I (cocopeat + EC 3.5-1), J (sawdust + EC 1.5-1), K (sawdust + EC 2.5-1), L ( sawdust + EC 3.5-1) with repeated 3 times. The results showed that the combination of organic growing media and EC value of the nutrient significantly affected the parameters of plant height, leaf number, root length, fresh weight, marketable weight, and leaf area of Broadbeaked mustard (Brassica narinosa L.H. Bailey) pagoda variety in hydroponic wick system. Treatment I (cocopeat + EC 3.5-1 gave the highest yield on an average fresh weight of 187.08 g, a marketable weight of 141.08 g.Â Keywords: Planting media; EC; Broadbeaked Mustard; Hydroponics Wick System